REPEAT OFFENDERS CONVICTED OF DRUG CRIMES AT SUKADANA CLASS IIB STATE PRISON - Fazlullah Bima Vallery; Mulyani Rahayu (Universitas Nusa Cendana, 2026)
This study examines the tendency of recidivism among narcotics prisoners at the Class IIB Sukadana State Detention Center, motivated by the persistently high rate of reoffending in Indonesia despite the implementation of correctional programs. The research aims to identify the internal and external factors influencing recidivism and to evaluate existing efforts to reduce its occurrence. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation involving correctional officers and recidivist inmates. The findings reveal that recidivism is driven by a combination of internal and external factors. Internal factors include low self-control and emotional instability, while external factors involve peer influence and socio-economic pressures that encourage individuals to return to criminal behavior. The study also finds that rehabilitation efforts, such as skills training and moral development programs, have contributed positively to reducing the tendency of recidivism. However, these programs are not yet fully optimal and require further strengthening to achieve more sustainable outcomes. In conclusion, reducing recidivism among narcotics inmates requires a more comprehensive rehabilitation system that addresses both psychological and social dimensions. Strengthening program quality, along with improved support systems during and after incarceration, is essential to ensure long-term behavioral change and successful reintegration into society. Keywords: Recidivism; Narcotics Prisoners; Detention Center; Internal Factors; External Factors